2020
DOI: 10.1002/cam4.2844
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LOC285194 modulates gastric carcinoma progression through activating Wnt/β‐catenin signaling pathway

Abstract: Emerging evidences have revealed long noncoding RNAs (lncRNAs’) critical roles in diverse human carcinoma. Among these cancers, lncRNA LOC285194 has been extensively investigated in several types of carcinomas in the recent years. Nevertheless, the biological function, clinical relevance, and the influence of LOC285194 in gastric cancer (GC) are not fully understood. The present study aims to explore the biological function of LOC285194 in the progression and development of GC. First, LOC285194 expressions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Experimental research found that LOC285194 overexpression inhibited cell proliferation and induced apoptosis in vascular smooth muscle cells (VSMCs) in vitro, and vice versa [23]. In gastric cancer MKN45 and HGC-27 cells in vitro and in vivo, LOC285194 overexpression suppressed cell proliferation and promoted cell apoptosis [24].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental research found that LOC285194 overexpression inhibited cell proliferation and induced apoptosis in vascular smooth muscle cells (VSMCs) in vitro, and vice versa [23]. In gastric cancer MKN45 and HGC-27 cells in vitro and in vivo, LOC285194 overexpression suppressed cell proliferation and promoted cell apoptosis [24].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [ 26 ] have reported that TYRO3 promotes cell growth and metastasis through activating the Wnt/ β -catenin pathway in GC. Zhong et al [ 27 ] have suggested that LOC285194 could facilitate GC progression through the activation of the Wnt/ β -catenin pathway. In the present study, we explored the effect of BASP1 on the expression of WT1, Wnt, and β -catenin in GC cells by qRT-PCR and western blot assays.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the mechanisms that regulate VSMC apoptosis potentially may lead to novel therapeutic approaches that are more efficacious for these patients. Previous works showed that LOC285194 overexpression induced cell apoptosis in gastric carcinoma [ 28 ], pancreatic cancer [ 29 ] and colon cancer [ 10 ]. In the present study, we demonstrated that LOC285194 overexpression significantly induced A7r5 cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%